The Word and the Spirit – Michael Welker’s theological hermeneutics Part 1 - Van der Westhuizen, Henco (Stellenbosch Theological Journal, 2016)
In this essay it will be argued that the biblical traditions, or the relation between the Spirit and the biblical traditions, can be understood as the basis, the seedbed, that on which Welker builds his realistic theology in general, and his theology of the Spirit in particular. Welker himself writes in his main work on the Spirit, Gottes Geist. Theologie des Heiligen Geistes, translated as God the Spirit, that the key trait of his theology is its biblical character. He even regards this work to be the first comprehensive biblical theology of the Spirit. This polemical motive in his theology, where a creative and truly complex conception of the Spirit is related explicitly to the biblical traditions, indeed, to the Word of God, will be clarified in the course of this essay. In the first part of this essay, it is shown that for Welker, the Word of God is not to be confused with the human word. In the light of the depth of the Spirit, this word is revealed to be deficient. Against the background of this differentiation the essay focuses on the biblical traditions, i.e. the Word of God. In order to understand Welker’s complex understanding of the Word of God, what he refers to as the fourfold weight of the biblical traditions is differentiated in the light of a general understanding of what could be conceived as a “biblical theology”.